Pattern Of Temporomandibular Joint Disorders And Associated Intra-Oral Findings Among Patients Reporting To Oral and Maxillofacial Surgery OPD, With History Of Psychiatric Illness In A Tertiary Care Hospital Of Taxila Cantt: Temporomandibular Joint Disorders and Intra-Oral Findings in Psychiatric Patients - Mehdi, Syed Zuhair; Siddiq, Maimoona; Moin, Sadia; Khan, Sarosh; Gillani, Syeda Rabia Rahat; Khan, Umar Farooq (Pakistan Journal of Health Sciences, 2024)
Temporomandibular joint illness impairs normal existence. Many disagree on this condition's cause. To comprehend this illness, know the signs. Understanding the prevalence of temporomandibular disorder will help people prevent them and schedule regular temporomandibular joint exams. Objective: To observe the pattern of temporomandibular joint disorders and associated intra-oral signs and symptoms among patients who are being treated for psychiatric illnesses and mental health issues. Methods: This prospective, cross-sectional study was conducted at the dental college HITEC-IMS Taxila Cantt from 1st September 2022 to 31st December 2023 and comprised of 181 patients. A detailed history of para-functional habits, headache, otalgia, smoking and stress was acquired along with a clinical examination of joint clicking, and occlusal variation. Fisher's exact test and pearson's chi-square found factor connections. Results: There were 112 (61.9%) females and 69 (38.1%) males in all patients. The patients mean age was 33.7 ± 10.47 years and had a mean BMI 24.12 ± 6.26 kg/m2. Among the symptoms that patients experienced, 125 (69.1%) heard noises in their joints, while 116 (64.1%) of the total reported feelings of emotional stress or strain. Most symptoms were more common in women. Men showed a substantial connection (p<0.005) between para-functional habits and stress/tension. Age also correlated with occlusal variation, joint sound, missing teeth, mastication side, parafunctional behaviors, tension, and stress. Conclusions: The study indicated that temporomandibular disorders were more common in women. Psychiatric patients most often complained of headache, clicking, and limited mouth opening.